SAFE-CGRP study: multicenter retrospective evaluation of the safety of CGRP pathway–targeting monoclonal antibodies in migraine with relevant comorbidities or conditions excluded from trials - Sanabria-Gago, Cristina; Lázaro, Iris Fernández; Heredia, Patricia; Sánchez-Soblechero, Antonio; Ros, Alberto Lozano; Buzo, Elisa Luque; Osorio, Yesica González; Guerrero-Peral, Ángel; Gonzalez-Martinez, Alicia; Azorín, David García; Latorre, Germán; Calle, Carlos; et al. (Frontiers in Neurology, 2025)
IntroductionMonoclonal antibodies (mAbs) targeting calcitonin gene-related peptide (CGRP) have shown efficacy in the treatment of migraine. However, certain comorbidities have been excluded from clinical trials or may pose potential risks, despite not being formal contraindications. This study aimed to assess the safety of anti-CGRP or anti-CGRP receptor mAbs in real-world patients with such conditions.MethodsA retrospective multicenter study was conducted across 11 headache units in Spain. Patients with relevant or trial-excluded comorbidities who received at least one anti-CGRP or anti-CGRP receptor mAb were included.ResultsOf 2,042 evaluated patients, 353 had at least one comorbidity. The mean treatment duration was 12.7 months [standard deviation (SD) = 8 months]. A total of 53 conditions were included: 202 had autoimmune diseases, 163 presented vascular risk factors or diseases [body mass index (BMI) > 30: 15.2%, diabetes: 5.38%, stroke/transient ischemic attack (TIA): 3.08%, cardiac ischaemic disease: 1.44%], of which 23 had moderate-to-high cardiovascular risk (Framingham scale); 23 had pulmonary diseases, 71 had a history of cancer, 12 were immunosuppressed, and 16 had other conditions. In 12% of cases, disease control was suboptimal after treatment initiation, without a causal relationship to the mAb. A possible treatment-related worsening was observed in 14 cases: four with arterial hypertension worsening, seven with Raynaud’s syndrome, two with arthritis flares, and one hereditary angioedema; all improved upon treatment discontinuation. No severe adverse events were reported.DiscussionIn this study, treatment with monoclonal antibodies acting on the CGRP pathway showed a favorable safety profile in patients with complex clinical conditions not represented in clinical trials, with no serious adverse events observed during extended follow-up. These findings support their use in real-world clinical settings, although further studies are needed to confirm their long-term safety.